'I Failed to Work Hard': Reasons for Secondary School Dropout among Muslim Men in Delhi. (January 2020) - Salman, Aashti
This article aims to understand the reasons and experiences which contribute to dropout among Muslims in India at the secondary school level (grades IX–XII). The focus of this article is low-income Muslim men, who have left school at the secondary level, in a predominantly Muslim neighbourhood of Jamia Nagar, Delhi. The context of this article is set by the seminal Sachar Committee Report which highlights the educational disadvantages of Muslims, categorising their school dropout rates as 'worrisome'. The findings of this article are partially consistent with previous research. In the final instance, the Muslim men in Jamia Nagar linked their school leaving to their personal failure: in terms of their inability to maintain interest in studies/failing to clear a grade. There was a strong value attached to hard work, which men felt they lacked, and this was cited as the reason for their personal failure in school. In the process of constructing this narrative, family experiences were downplayed. School experiences were singled out by men as not affecting their decision to drop out. Another striking finding of this study is the relationship between self-employment and the decision to drop out.